The Use of Problem-Based Learning to Improve Students’ Reading Comprehension at the First Grade Students of Senior High School 1 of Middle Halmahera - Greselia Kaganang (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2019)
This research was conducted to see how the use of PBL could improve the students’ reading comprehension, especially the students who participated in this research. Designed as a classroom action research, 21 students in the mentioned school in the title were involved. The researcher was helped by a collaborator handing an observation sheet. This research took two cycles with four stages in each cycle. The result indicated that before the use of PBL as learning model, the participants-students’ reading scores were low and some of them were not passed the passing grade. After the use of PBL, the students’ scores increased and most of the students passed the passing grade. The researcher also gathered the students’ positive responses on the use of PBL in English classroom.